Mesoscale organization of titania thin films enables oxygen sensing at room temperature. Issue 45 (7th November 2017) - Rassu, Pietro; Malfatti, Luca; Carboni, Davide; Casula, Maria F.; Garroni, Sebastiano; Zampetti, Emiliano; Macagnano, Antonella; Bearzotti, Andrea; Innocenzi, Plinio
Abstract : We developed an oxygen sensor based on mesoporous titania films working at RT under UV irradiation. Due to larger surface area and number of defects, the mesoporous film exhibits a response higher than dense titania. Abstract : The application of titania materials to gas sensing devices based on thin films are of limited utility because they only operate at a high working temperature and exhibit in general a low sensitivity. To overcome these constraints, a new type of oxygen sensor based on mesoporous titania thin films working at room temperature under UV irradiation has been developed. The increased density of charge carriers induced by the photoconductive effect, has been used to enhance the sensitivity of the thin oxide layers. Mesostructured titania films have been prepared via self-assembly and thermal processing to remove the organic template obtaining anatase nanocrystals. The mesoporous films show a striking decrease of the current in the presence of oxygen that acts as an electron scavenger. Mesoporous samples exhibit a much higher response with respect to dense titania, due to the higher surface area and the larger number of surface defects.